Pengendalian Pecah Kulit Buah Duku (Lansium domesticum Corr.) dengan Kalsium Karbonat pada Lahan Suboptimal - Budiyati Ichwan; Mapegau Mapegau; Irianto Irianto (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
The broken skin on fruit was the main problem on quality of duku. The availability of calcium on soil presumable having an effect on broken skin on fruit of duku. A field experiment to evaluated the effect of calcium in controlling the broken skin on fruit of duku was carried out in Kumpeh Ulu, Muaro Jambi, Jambi from Januari 2009 through to Februari 2010. The experiment was conducted on suboptimal land with soil acidity is 4.97 (pH H2O). Randomized Completely Block Design was used with 3 replications. The treatments consisted of 4 calcium carbonat doses i.e. 0 ton/ha, 1.0 ton/ha, 1.5 ton/ha and 2.0 ton/ha. The result showed that calsium carbonat doses decresing percentage of broken skin on fruit of duku and increasing concentration of hemicelluloce on fruit skin and fresh weight of fruit, calcium carbonat dose 2 ton/ha gave the lowest percentage of broken skin and the highest hemicelluloce concentration on fruit of duku. The highest of fresh weight of fruit at calcium carbonat dose 1 ton/ha.